Faculty Publication Activity and Resources for Its Increase - Ashot R. Alaverdov (Moscow Polytechnic University, 2019)
The article discusses the current situation in the Russian higher school system related to the publication activity of faculty, including publications in journals indexed in international citation databases Scopus and Web of Science. The author argues that the vast majority of scientific and pedagogical workers of Russian universities, especially those teaching social and economic disciplines, are unable to provide the necessary number of such publications required by the administration, due to both organizational and financial reasons. In order to ensure at least a relative balance between the interests of the faculty and their employer, it is proposed to create new structural entities in large public and private universities - centers for support of the publication activity of teachers. The author has developed a project of standard organizational structure of management for this Center, as well as an algorithm of its work and the main functions of its divisions.